Kesiapan Tenaga Kesehatan dalam Menghadapi Bencana pada Tahap Mitigasi di Puskesmas Sitiarjo Kabupaten Malang: Readiness of Health Personnel in Facing Disaster at the Mitigation Stage at the Sitiarjo Puskesmas, Malang Regency - Lilis Sulistiya Nengrum (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Indonesia has tremendous disaster potential, from floods, landslides, earthquakes, fire eruptions, prolonged droughts, hurricanes, and fires. Mitigation is to reduce the risks posed by disasters. Disaster mitigation focuses on reducing the impact of threats to reduce the likelihood of adverse effects from disasters. A health worker is any person who devotes himself to health and has knowledge and skills through education in health and for certain types requires the authority to undertake health efforts. This study aims to describe health workers in dealing with disasters at the mitigation stage at the Puskesmas Sitiharjo-Sumbermanjing Wetan Malang Regency. This research uses Cross Sectional research method. The treatment of this research is by giving questionnaires to respondents. The analysis of the readiness level of health personnel in the face of ready-prepared disaster risk reduction is 88%, ready enough 12%, and at the prevention of ready disasters 84%, ready enough 16%, and on education and training disaster prepared 12%, quite ready 88%, And in disaster preparedness planning that is ready 88%, ready enough 12%. This study found that health workers are less in the education and training category. Based on the results of this study can be advised puskesmas Sitiarjo for training education for health workers.